Requirements for Achieving Organizational Excellence An entry into business organizations - Kharmouche Mouna; Bahri Saber (Journal of North African Economies, 2025)
Among the recent organizational behaviors that have emerged is organizational excellence Where do organizations strive to achieve them to achieve their goals in a way that achieves productive productivity, Especially since organizational excellence has become the main guarantor of the organization's survival and continuity, So many organizations incite to achieve organizational excellence in various aspects, In order to achieve this, there must be several basic requirements for achieving organizational excellence in business organizations. We will try in this place Address the most important of these requirements, which play a pivotal role and push the organization toward organizational excellence.